Les Orangs-Outans fossiles : apport des dernières découvertes au Viêtnam - Anne-Marie Bacon; Fabrice Demeter; Vu The Long (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
The discovery of the first complete skeleton of a fossil orang-utan from the Hoa Binh province in Vietnam brings original information about the evolution of these asiatic apes. Dental morphology and morphometry of the adult individual are compared with those of known taxa (modern and fossil), whereas its body proportions are compared with those of the two modern subspecies, from Borneo (Pongo pygmaeus pygmaeus) and from Sumatra (Pongo pygmaeus abelii). Hypothetical causes for the extinction of orangs-utans on the continent are mentioned.